Analisis Kinerja Keuangan Menggunakan Analisis Arus Kas Pada Depot Air Minum Sangsa - Rantika Camila Bunga; Tuti Fitriani (JURNAL ULET (Utility, Earning and Tax), 2023)
The purpose of this study was to determine the financial performance of the Depot Air Minum Sangsa based on cash flow analysis. This research uses descriptive research method. Data collection techniques in this study are interview and documentation techniques. Data analysis instruments in this study use the Cash Return on Sales Ratio, Cash Flow to Net Income Ratio, Cash Reinvestment Ratio. The results of this study show that the financial performance of Depot Air Minum Sangsa in converting every IDR of sales into cash is classified as good, the ability to convert every IDR of net profit into cash is classified as not good, the ability to invest and expand is classified as not good due to high prive. So that the overall performance of the Depot Air Minum Sangsa, seen from the analysis is classified not good.